SMALL AND MEDIUM MICRO ENTREPRISES INNOVATION STRATEGIES IN EFFORTS TO FACE THE INDUSTRY REVOLUTION 4.0 - Tranggono; Egan Evanzha Yudha Amriel; Endang Sholihatin; Nanang Haryono (Journal of Economics, Business, and Government Challenges, 2021)
Micro, small and medium enterprises still rely on conventional ways ofdoing business. On the other hand, rapid digitalization is integrated with theeconomy and trade, giving birth to the industrial revolution 4.0. If micro, smalland medium enterprises do not want to innovate, they will be disrupted. Theresearch objectives are to describe the innovation strategies of micro, small andmedium enterprises in increasing competitiveness in facing the industrialrevolution 4.0; and also identify factors that hinder the innovation of micro, smalland medium enterprises in increasing competitiveness in facing the industrialrevolution 4.0. The method used in this research is qualitative. The researchlocation is in the area of ​​micro, small and medium enterprises in Gresik Regencyand Sidoarjo Regency. The conclusion of this research is(a) innovation strategiesfor micro, small and medium enterprises in increasing competitiveness in facingthe industrial revolution 4.0 through marketing with e-commerce marketingthrough social networking media. One of the strategies is product innovation.(b)Furthermore, the factors that hinder innovation are human resources, capital toinnovate, a narrow owner's mindset, and the use of technology that is still simple.lack of strategic partners for innovation, managementmicro small and MediumEnterprises who are kinship and less professional, and lack of permits micro smalland Medium Enterprises.